Accuracy of acute burns diagnosis made using smartphones and tablets: a questionnaire-based study among medical experts. - Blom, Lisa; Boissin, Constance; Allorto, Nikki; Wallis, Lee; Hasselberg, Marie; Laflamme, Lucie (BMC Emergency Medicine, 2017)
Background: Remote assistance for burns by medical experts can support nurses and general physicians in emergency care with diagnostic and management advice. Previous studies indicate a high diagnostic accuracy based on images viewed on a computer screen, but whether image-based analysis by experts using handheld devices is accurate remains to be determined.Method: A review of patient data from eight emergency centres in the Western Cape, South Africa, revealed 10 typical cases of burns commonly seen in children and adults. A web-based questionnaire was created with 51 images of burns representing those cases. Burns specialists from two countries (South Africa and Sweden (n = 8 and 7 respectively)) and emergency medicine specialists from South Africa (n = 11) were contacted by email and asked to assess each burn's total body surface area (TBSA) and depth using a smartphone or tablet. The accuracy and inter-rater reliability of the assessments were measured using intraclass correlation coefficients (ICC), both for all cases aggregated and for paediatric and adult burn cases separately. Eight participants repeated the questionnaire on a computer and intra-rater reliability was calculated.Results: The assessments of TBSA are of high accuracy all specialists aggregated (ICC = 0.82 overall and 0.81 for both child and adult cases separately) and remain high for all three participant groups separately. The burn depth assessments have low accuracy all specialists aggregated, with ICCs of 0.53 overall, 0.61 for child and 0.46 for adult cases. The most accurate assessments of depth are among South African burns specialists (reaching acceptable for child cases); the other two groups' ICCs are low in all instances. Computer-based assessments were similar to those made on handheld devices.Conclusion: As was the case for computer-based studies, burns images viewed on handheld devices may be a suitable means of seeking expert advice even with limited additional information when it comes to burn size but less so in the case of burn depth. Familiarity with the type of cases presented could facilitate image-based diagnosis of depth.